A new species of Hypostomus Lacépède, 1803 (Siluriformes: Loricariidae) from the upper rio Paraná basin, Southern Brazil - Jerep,Fernando C. (2007)
A new species of Hypostomus with large and spaced light roundish spots is described from the upper rio Paraná basin. Hypostomus multidens new species is distinguished from all remaining congeners with light spots on a darker background by two independent characters: the presence of teeth with two symmetrical cusps, and a high tooth number in each dentary (122267, mean 196.8) and premaxilla (115-260, mean 190.8).